2021
DOI: 10.3791/62072
|View full text |Cite
|
Sign up to set email alerts
|

Twin-Screw Extrusion Process to Produce Renewable Fiberboards

Abstract: A versatile twin-screw extrusion process to provide an efficient thermo-mechanochemical pre-treatment on lignocellulosic biomass before using it as source of mechanical reinforcement in fully bio-based fiberboards was developed. Various lignocellulosic crop by-products have already been successfully pre-treated through this process, e.g., cereal straws (especially rice), coriander straw, shives from oleaginous flax straw, and bark of both amaranth and sunflower stems.The extrusion process results in a marked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…For example, the paper (Evon et al, 2021) describes a developed universal twin-screw extrusion presses to provide efficient thermo-mechanical-chemical pretreatment of lignocellulose biomass before using it as a source of mechanical hardening in fully bio-fibre boards. Various lignocellulose byproducts of crop production have already been successfully pretreated using this process, such as grain straw (especially rice), coriander straw, flax straw pods, and the bark of amaranth and sunflower stalks (Evon et al, 2021). Its mixing ability and the ability to add various components at the end of the screw profile are also advantages of this extrusion press.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the paper (Evon et al, 2021) describes a developed universal twin-screw extrusion presses to provide efficient thermo-mechanical-chemical pretreatment of lignocellulose biomass before using it as a source of mechanical hardening in fully bio-fibre boards. Various lignocellulose byproducts of crop production have already been successfully pretreated using this process, such as grain straw (especially rice), coriander straw, flax straw pods, and the bark of amaranth and sunflower stalks (Evon et al, 2021). Its mixing ability and the ability to add various components at the end of the screw profile are also advantages of this extrusion press.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As for shives from textile flax, they could be used as animal litters because of their high water absorbency [15]. Recent works have nevertheless shown that shives from linseed flax could be also used to replace wood particles in the manufacture of boards [15,16]. Extrusionrefining pre-treatment of shives increases their mean aspect ratio and, consequently, the mechanical strength of the boards, and proteins from linseed cake can even be added as naturel binder to further increase this strength [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have nevertheless shown that shives from linseed flax could be also used to replace wood particles in the manufacture of boards [15,16]. Extrusionrefining pre-treatment of shives increases their mean aspect ratio and, consequently, the mechanical strength of the boards, and proteins from linseed cake can even be added as naturel binder to further increase this strength [16]. On the basis of their usage properties, such materials could find various applications, e.g., intermediate containers, furniture, domestic flooring, shelving, general construction, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations